50.7k views
5 votes
9x + 2y = 30
6x + 4y = 12

User Josemmo
by
4.8k points

2 Answers

6 votes

Answer:

For graphing, your answer is...(4,-3)

Explanation:

1.Subtract 9x on both sides...

2y=30-9x

6x+4y=12

2. Divide each term by 2, then simplify...

-Divide... 2y=30-9x by 2.

2y/2=30/2+-9x/2

6x+4y=12

3. Reduce expression by...cancelling your common factors...

Cancel...2 from 2y/2

6x+4y=12

Divide y by 1...

y=30/2+-9x/2

6x+4y=12

4.Simplify each term...

-Divide thirty by two.

y=15+-9x/2

6x+4y=12

-Move your negative in the front of your fraction.

y=15 - 9x/2

6x+4y=12

5. Subtract 6x from both sides of your equation...

y=15 - 9x/2

4y=12-6x

6. Divide each term by four...divide terms in 4y=12-6x by four...

y=15 - 9x/2

4y/4=12/4+-6x/4

-Reduce expression by cancelling common factors in 4y/4...

Divide y by one...

y=15 - 9x/2

y=12/4+-6x/2

7. Simplify each term...Divide twelve by four...

y=15 - 9x/2

y=3+-6x/4

-Reduce expression by cancelling all common factors...

Your factor is 2 our of -6x...

y=15 - 9x/2

y=3+2(-3x)/4

-Cancel the common factors.. two out of four...

y=15 - 9x/2

y=3+2(-3x)/2(2)

-Cancel common factors again...

y=15 - 9x/2

y=3+-3x/2

8. Move your negative over to the front of your fraction...

y= 15 - 9x/2

y=3 - 3x/2

You get... (4,-3)

I hope this helps you and I also do hope that this is what you are looking for! If not, then my bad! Good luck, mate!

User Cerad
by
5.2k points
5 votes

1. Simplifying

9x + 2y = 30

Solving

9x + 2y = 30

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2y' to each side of the equation.

9x + 2y + -2y = 30 + -2y

Combine like terms: 2y + -2y = 0

9x + 0 = 30 + -2y

9x = 30 + -2y

Divide each side by '9'.

x = 3.333333333 + -0.2222222222y

Simplifying

x = 3.333333333 + -0.2222222222y

-------------------------------------------------------------------------------------------

2. Simplifying

6x + 4y = 12

Solving

6x + 4y = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4y' to each side of the equation.

6x + 4y + -4y = 12 + -4y

Combine like terms: 4y + -4y = 0

6x + 0 = 12 + -4y

6x = 12 + -4y

Divide each side by '6'.

x = 2 + -0.6666666667y

Simplifying

x = 2 + -0.6666666667y

User Jacobz
by
4.4k points